Upaya mantan Istri dalam menuntut Nafkah Anak Pasca Perceraian - Muizzuddin, Ahmad Haris (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstrak : This research uses a normative juridical approach with analytical descriptive research specifications. This research focuses on document or library research by looking for theories, views that are correlated and relevant to the problem to be researched and to complement the data obtained from document and library research, field research is carried out, namely from sources. Efforts that can be made by the Religious Courts regarding the implementation of decisions, especially those concerning the father's obligations/responsibilities for his child's support, must be differentiated between before and after the divorce vow is pronounced by the husband. Before the husband pronounces the divorce vow in front of the court, the Religious Court, in this case the Panel of Judges, has the authority to supervise and force the husband to first fulfill his obligations in accordance with the ruling, namely those relating to the rights of the wife being divorced, in this case in the form of iddah maintenance, madhiyah, mut'ah, child support including child support. After the husband's vow of divorce is pronounced in court, the Religious Court is passive, if there is no request for execution, the Religious Court considers the decision that has been handed down to be unproblematic and can be implemented voluntarily. Keywords: marriage, decision, child support. Abstrak Penelitian ini menggunakan metode pendekatan yuridis normatif dengan spesifikasi penelitian deskriptif analitis. Penelitian ini menitikberatkan pada penelitian dokumen atau kepustakaan dengan mencari teori-teori, pandangan-pandangan yang mempunyai korelasi dan relevan dengan permasalahan yang akan diteliti dan untuk melengkapi data yang diperoleh dari penelitian dokumen dan kepustakaan maka dilakukan penelitian lapangan yaitu dari sumber-sumber. Upaya yang dapat dilakukan oleh Pengadilan Agama berkenaan dengan pelaksanaan putusan khususnya yang menyangkut kewajiban/tanggung jawab ayah terhadap nafkah anaknya, harus dibedakan antara sebelum dan sesudah ikrar talak diucapkan oleh suami. Sebelum suami mengucapkan ikrar talak di depan pengadilan, Pengadilan Agama dalam hal ini Majelis Hakim berwenang untuk mengawasi dan memaksa suami agar terlebih dahulu memenuhi kewajibannya sesuai dengan amar putusan, yaitu yang berkenaan dengan hak-hak istri yang ditalak, dalam hal ini berupa nafkah iddah, nafkah madhiyah, mut’ah, nafkah anak termasuk nafkah anak. Setelah ikrar talak oleh suami diucapkan di pengadilan, Pengadilan Agama bersikap pasif, apabila tidak ada permintaan eksekusi, Pengadilan Agama menganggap putusan yang telah dijatuhkan tidak bermasalah dan dapat dilaksanakan dengan sukarela. Kata kunci : perkawinan, putusan, nafkah anak.